The effect of compressibility on the primary global instability of unforced laminar separation bubbles - Gennaro, E. M. [UNESP]; Souza, B. D.P. [UNESP]; Rodríguez, D. (Springer Nature, 2019)
Laminar separation bubbles present a three-dimensional self-excited instability mechanism which leads to the appearance of spanwise-periodic structures. In incompressible flow, this mechanism was found to become active at conditions in which wave-like, two-dimensional perturbations are only convectively unstable. In the absence of continuous external excitation, the three-dimensional instability is expected to dominate the flow dynamics and initiate the laminar-turbulent transition. This work extends previous analyses by incorporating the effect of compressibility at subsonic conditions. Two-dimensional numerical simulations of a flat-plate boundary layer with a prescribed free-stream deceleration and acceleration are carried out to obtain a set of model laminar separation bubbles. A linear stability analysis is applied then, to study the influence of Reynolds and Mach numbers on the three-dimensional instability.
Keywords: Boundary layers; Compressible flow; Global instability; Laminar separation bubbles